2013
DOI: 10.1159/000350356
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Mitral Regurgitation in Heart Failure with Reduced or Preserved Left Ventricular Ejection Fraction

Abstract: Secondary mitral regurgitation (MR) has been extensively studied in heart failure due to reduced ejection fraction. In contrast, the occurrence and the pathogenesis of secondary MR are much less known in heart failure with preserved ejection fraction (HFpEF). The present review aimed at describing this common but ignored feature of HFpEF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 60 publications
0
37
0
1
Order By: Relevance
“…Not surprisingly, the severity of LVDD is as much a determinant of PH in HFpEF as it is in HFrEF 165, 166, 167. In addition, functional mitral regurgitation attributable to mitral leaflets tenting resulting from elevated LA pressure plays a role in the pathogenesis of PH in HFpEF 168, 169, 170, 171, 172. The contribution of functional mitral regurgitation to PH is greater in the decompensated state, when LA pressure is markedly elevated, than in the compensated state 172.…”
Section: Ph Phenotypementioning
confidence: 99%
“…Not surprisingly, the severity of LVDD is as much a determinant of PH in HFpEF as it is in HFrEF 165, 166, 167. In addition, functional mitral regurgitation attributable to mitral leaflets tenting resulting from elevated LA pressure plays a role in the pathogenesis of PH in HFpEF 168, 169, 170, 171, 172. The contribution of functional mitral regurgitation to PH is greater in the decompensated state, when LA pressure is markedly elevated, than in the compensated state 172.…”
Section: Ph Phenotypementioning
confidence: 99%
“…There is evidence that mitral insufficiency although more frequent in HF reduced ejection fraction (HFrEF) may also occur in HFpEF. 17,18 Although the definition is universal, the clinical PH phenotype that is associated with HFpEF may be variable, considering that PH may set in acute HF or chronic HF. In acute HF, it may develop in acutely developing (de novo) or chronic acutely exacerbating HF (on CHF) as a first clinical manifestation or superimposed.…”
Section: Definition Epidemiological Data and Diagnosismentioning
confidence: 99%
“…EF, accepted as an indicator of myocardial contractility, may be unusually high even in the early course of MR because it is inversely related to afterload [3,6]. Many previous studies reported that patients undergoing surgery before developing contractile dysfunction and dilatation had better postoperative clinical outcomes in the short and long term than those with contractile deficiencies [[6], [9]].…”
Section: Discussionmentioning
confidence: 99%
“…Volume overload causes heart muscle hypertrophy through the addition of new sarcomeres in myocardial cells. Nonetheless, left ventricular (LV) ejection fraction (EF) may be intact even though myocardial dysfunction develops as a consequence of hypertrophy [3]. Diminished EF accuracy when assessing the LV systolic function in MR has led to an ongoing search for more accurate and dependable indices as potential prognostic tools.…”
mentioning
confidence: 99%